Modeling Production Decisions : A Decision Supporting Tool - Al Koubaisy, M. M.; Al Utaibi, Ghassan A. (جامعة العلوم والتكنولوجيا, 2005)
تهدف هذه الدراسة إلى دراسة وتحليل مشاكل الإنتاج التي تواجه إدارة أحد مصانع الصلب لقد تمت دراسة العمليات المختلفة في الصنع وكلفها وذلك من أجل تحديد العلاقات الوظيفية التي تربطها بشكل دقيق لقد بينت الدراسة أن هذا النوع من المشكلات يواجه إدارات الإنتاج بشكل مستمر مما يبين الحاجة إلى الحصول على معلومات جديدة باستمرار واستيعابها قبل إحراز أي تقدم نحو حل المشكلات لقد تم في هذه الدراسة عرض النماذج المطلوبة لدعم نشاطات اتخاذ القرار في الصنع وكذلك التوصيات الكفيلة بتحقيق النتائج المرجوة The purpose of this study is to investigate and analyze production problems facing management at a steel plant. Various parts of the plant and associated costs are investigated in order to determine the precise functional relationships that hold between them. The study reveals that managers are frequently faced with this problematic situation when it is necessary to have and absorb new information about an industrial process before being able to make progress with solving the problem. Models are presented to achieve the required results and recommendations are given for supporting management decision making at the plant.
أصل المقال منشور باللغة الإنجليزية
Keywords: إدارة الشركات -- مستخلصات الأبحاث -- صناعة الحديد والصلب -- الإنتاج الصناعي -- المصانع -- المشاكل الإدارية -- اتخاذ القرارات